Nationalism: A Border–Making Ideal - Giri, Pradip Kumar (KMC Research Journal, 2019)
In this research article, my purpose and goal will be to show nationalism as a border-constructing ideal. Various different types of nations and nationalities, divide humans in different nationality groups. Nationalism, as a term, refers to a doctrine or political movement that holds a nation, usually defined in terms of ethnicity or culture, has the right to constitute an independent or autonomous political community based on a shared history and common destiny. In the true sense, nationalism does not cover all humans but just a community in which people share common history, culture and so on. It is concerned mainly with the creation of a state and its maintenance and strengthening. It can be understood as a political program that sees creation and maintenance of a fully sovereign state owned by a given ethno-national group, people or nation, as a major duty of each member belonging to the group. This article incorporates the ideas and theoretical insights of various theorists/writers towards nationalism. I introduce nationalism, discuss, very briefly, the seven types of nationalism presented in contemporary literature, present an overview of ‘nation,’ ‘ state’ and ‘nation-state,’ and draw the conclusion that nationalism is a boundary making ideal. I use qualitative technique in preparing this article prove my claim that nationalism makes wall and divides people in different groups.